Olympic qualification; Top 8 study - Callan, M.; Lascau, F. D. (2013)
The paper focuses on the top eight (Top 8) players in the International Judo Federation (IJF) World Ranking List (WRL), as used for direct qualification to the London 2012 Olympic Games. These players made up the seeds for the Olympic Games. The sample was drawn from the official IJF lists of direct and indirect qualifiers. 30 nations achieved a Top 8 placing, JPN, FRA, RUS, BRA and KOR all achieved 10 or more seeds. 598 834 points were required to achieve a Top 8 position. The best players appear to be very efficient at points collection, and manage to achieve `valuable wins`. 40% of the sample, were previously medallists in the World Junior Championships. The average time since this achievement was 7 years. Significant gains of over 100 places in the WRL are possible over the two year qualification period. The average improvement in the sample was 28 places. A number of recommendations for further research were made which could impact on performance success in the 2016 Rio de Janiero Olympic Games.